The Timing Effects of Reward, Business Longevity, and Involvement on Consumers’ Responses to a Reward Program - Sukoco, Badri Munir; Lai, Meng-Kuan; Weng, Wan-Jou (ASEAN Marketing Journal, 2021)
The Timing Effects of Reward, Business Longevity, and Involvement on Consumers’ Responses to a Reward Program